Variability in the Aerobic Fitness-Related Dependence on Respiratory Processes During Muscle Work Is Associated With the ACE-I/D Genotype - Gasser, Benedikt; Frei, Annika; Niederseer, David; Catuogno, Silvio; Frey, Walter O.; Flück, Martin (Frontiers in Sports and Active Living, 2022)
Background: The efficiency of aerobic energy provision to working skeletal muscle is affected by aerobic fitness and a prominent insertion/deletion polymorphism in the gene for the major modulator of tissue perfusion, angiotensin converting enzyme (ACE-I/D). We assessed whether variability in the fitness state-dependent contribution of multiple aspects of oxygen transport to the development of muscle power, and the respective control coefficients, are associated with the ACE-I/D genotype. Methods: 25 females and 19 males completed a ramp test of cycling exercise to exhaustion during which serial steps of oxygen transport (VO2, VE, Q, SpO2, SmO2 and THb in Musculus vastus lateralis and Musculus gastrocnemius, RER), blood lactate and glucose concentration, were continuously monitored. The contribution/reliance of power output on parameters of oxygen transport was estimated based on the slopes in Pearson’s moment correlations (|r| > 0.65, p<0.05) vs power values over the work phase of the ramp test, and for respective fractional changes per time (defining control coefficients) over the rest, work and recovery phase of the ramp test. Associations of variability in slopes and control coefficients with the genotype and aerobic fitness were evaluated with ANOVA. Results: All parameters characterizing aspects of the pathway of oxygen, except THb, presented strong linear relationships ((|r| > 0.70) to power output. Metabolic efficiency was 30% higher in the aerobically fit subjects (VO2peak ≥ 50 mL min-1 kg-1), and energy expenditure at rest was associated with the fitness state x ACE-I/D genotype, being highest in the fit non-carriers of the ACE D-allele. For VO2, VE and RER the power-related slopes of linear relationships during work demonstrated an association with aerobic fitness; being 30-40% steeper in the aerobically fit than unfit subjects. For VE the power-related slope also demonstrated an association with the ACE-I/D genotype. For DSmO2 in Musculus vastus lateralis, the power-related slope was associated with the interaction between aerobic fitness x ACE-I/D genotype Conclusions: Local and systemic aspects of aerobic energy provision stand under influence of the fitness state and ACE-I/D genotype. This especially concerns the association with the index of muscle’s mitochondrial respiration (SmO2) which compares to genetic influences of endurance training.